Dynamic Buffer Management for IPTV Video Players - Mendes, Marcos Paulo; Moreno, Marcelo Ferreira (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Due to recent technological evolution, the provision of IPTV services has grown considerably. One of the services normally included in IPTV is Linear TV, where audiovisual contents are made available in the form of program schedules. Another service is Video on Demand, where the viewer can perform actions like pause, play and seek (trick mode). In this context, challenges emerge regarding the distribution of multimedia content over these services. One of these challenges is specifically the user’s perception about the quality of the IPTV service, measured in terms of quality of experience (QoE). Thus, this article aims to analyze the problems that may occur when receiving Linear TV and VoD content and to propose solutions to these problems. Specifically, due to the congestion of transmission media or overload in the endpoints, a key issue is the statistical variation of time delay for multimedia content delivery (packet jitter). This paper’s proposal comprises a novel dynamic management of buffers in IPTV terminal devices, taking into account the characteristics of both Linear TV and VoD services.